Obtaining technological parameters for the preparation of nixtamalized products, type fried snacks, from high Andean cereals: Maize (Zea mays); Quinoa (Chenopodium quinoa); Kiwicha (Amaranthus caudatus). - Rodríguez Luque, Gisela Yvette (2014)
Objective: Develop nixtamalized products from the High Andean Grains (Corn, Quinoa and Amaranth). Method: A technological scientific research experimental design applied to determine the nixtamalization process high Andean grains. The proposed method is the nixtamalization process which involves the cooking of High Andean Grains (Quinoa, Amaranth and Corn) in an alkaline solution made with cal. To accomplish the removal of the pericarp, smooth grain texture and impart the characteristic flavor to nixtamalized products. Once cooked beans are ground to obtain a wet mass, which is rolled, cut, baked and fried. Before being packaged in good condition. Result: The right percentages of lime for nixtamalization of Quinoa and Amaranth were found, which were 1.5 % and 1 % respectively. Time and temperature suitable for cooking Quinoa and Amaranth was 15min. And 90 ° C for both grains. The time and temperature for baking nixtamalized corn dough was 7 min. And 180 °C. The frying time and temperature of the product was 1.5 min at 200 °C. Conclusions: With the experiments were able to establish a suitable method for the preparation of a new nixtamalized product, showing that it is a cost-effective and acceptance in the consumer population fried snack product.